Adjunctive Pharmacotherapies in Children With Asthma Exacerbations Requiring Continuous Albuterol Therapy: Findings From The Ohio Pediatric Asthma Repository - Shein, Steven L. (Hosp Pediatr, 2018)
OBJECTIVES: To identify associations between use of ipratropium and/or intravenous magnesium and outcomes of children hospitalized with acute asthma exacerbations and treated with continuous albuterol. METHODS: Secondary analysis of data from children prospectively enrolled in the multicenter Ohio Pediatric Asthma Repository restricted to only children who were treated with continuous albuterol in their initial inpatient location. Children were treated with adjunctive therapies per the clinical team. RESULTS: Among 242 children who received continuous albuterol, 94 (39%) received ipratropium only, 13 (5%) received magnesium alone, 42 (17%) received both, and 93 (38%) received neither. The median duration of continuous albuterol was 7.0 (interquartile range [IQR]: 2.8–12.0) hours. Ipratropium use was associated with a shorter duration of continuous albuterol (4.9 [IQR: 2.0–10.0] hours) compared with dual therapy (11.0 [IQR: 5.6–28.6] hours; P = .001), but magnesium use was not (7.5 [IQR: 2.5–16.0] hours; P = .542). In Cox proportional models (adjusted for hospital, demographics, treatment location, and respiratory failure), magnesium was associated with longer durations of continuous albuterol (hazard ratio, 0.54 [95% confidence interval: 0.37–0.77]; P < .001) and hospitalization (hazard ratio, 0.41 [95% confidence interval: 0.28–0.60]; P < .001), but ipratropium was not. CONCLUSIONS: Ipratropium and magnesium were both often used in children with severe asthma hospitalizations that required continuous albuterol therapy. Magnesium use was associated with unfavorable outcomes, possibly reflecting preferential treatment to patients with more severe cases and differing practices between centers. Given the high prevalence of asthma, wide variations in practice, and the potential to improve outcomes and costs, prospective trials of these adjunctive therapies are needed.